2021
DOI: 10.3390/cancers13040866
|View full text |Cite
|
Sign up to set email alerts
|

Precision Nutrition to Activate Thermogenesis as a Complementary Approach to Target Obesity and Associated-Metabolic-Disorders

Abstract: Obesity is associated to increased incidence and poorer prognosis in multiple cancers, contributing to up to 20% of cancer related deaths. These associations are mainly driven by metabolic and inflammatory changes in the adipose tissue during obesity, which disrupt the physiologic metabolic homeostasis. The association between obesity and hypercholesterolemia, hypertension, cardiovascular disease (CVD) and type 2 diabetes mellitus (T2DM) is well known. Importantly, the retrospective analysis of more than 1000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 213 publications
(249 reference statements)
0
10
0
Order By: Relevance
“…MiRNAs were found to be better regulated in obese patients following an MD [ 137 ]. Recent studies have shown that an MD reduces serum inflammatory markers as well as the incidence of stroke, CVD and breast cancer [ 138 , 139 ]. Moreover, MD was recommended as a diet that can help women with menopause-related symptoms and needs [ 140 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs were found to be better regulated in obese patients following an MD [ 137 ]. Recent studies have shown that an MD reduces serum inflammatory markers as well as the incidence of stroke, CVD and breast cancer [ 138 , 139 ]. Moreover, MD was recommended as a diet that can help women with menopause-related symptoms and needs [ 140 ].…”
Section: Discussionmentioning
confidence: 99%
“…β3-AR signalling. The relative roles and modes of regulation of GLUT1 versus GLUT4-dependent glucose uptake in thermogenic fat in vivo will require further investigation [116,[137][138][139][140].…”
Section: Thermogenesis Bmentioning
confidence: 99%
“…We previously showed dysregulation within the T2DM pathway in male Ts mice compared to 2N littermates at~6 MO [75]. Accordingly, we used Fr Ctx tissue, which receives a prominent cholinergic input from BFCNs to interrogate three protein hormones dysregulated in human MetS/IR and T2DM: APN, insulin and leptin [30][31][32][33] in trisomic mice, with the hypothesis that MCS would have a beneficial effect. APN levels were significantly downregulated by approximately two-fold in Ts Fr Ctx (mean 9.53 ng/mL; p < 0.001; Figure 1A) compared to 2N (mean 18.89 ng/mL).…”
Section: Protein Hormone Levels In Trisomic Mice and The Impact Of Mcsmentioning
confidence: 99%
“…MetS/IR as well as T2DM are recognized as risk factors for dementia associated with AD [29]. The protein hormones insulin, leptin and adiponectin (APN) are linked to MetS/IR, T2DM and the associated increased risk for AD pathology [30][31][32][33]. Studies in persons with DS have also shown dysregulation of these protein hormones [24,34].…”
Section: Introductionmentioning
confidence: 99%